2016
DOI: 10.1139/cjps-2016-0141
|View full text |Cite
|
Sign up to set email alerts
|

Organic selection may improve yield efficiency in spring wheat: A preliminary analysis.

Abstract: Organic spring wheat (Triticum aestivum L.) breeding programs have been initiated, yet yield efficiency and N economy research is limited. We evaluated the performance of advanced lines selected from an organic breeding program initiated in 2003. Fourteen F 8 and F 9 lines in 2009 and 11 lines in 2010 were compared with commercial (check) cultivars. Field experiments were conducted under organic management at four site-years in Manitoba and Saskatchewan. Combined analysis showed no difference in biomass accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Seed mass was significantly lower for farmer selections than for check cultivars (Table 6). Wiebe et al (2017) observed greater kernel production per unit area of land in organically selected lines compared with conventional check cultivars. Wiebe et al (2017) observed greater kernel production per unit area of land in organically selected lines compared with conventional check cultivars.…”
Section: Yield and Yield Componentsmentioning
confidence: 76%
See 3 more Smart Citations
“…Seed mass was significantly lower for farmer selections than for check cultivars (Table 6). Wiebe et al (2017) observed greater kernel production per unit area of land in organically selected lines compared with conventional check cultivars. Wiebe et al (2017) observed greater kernel production per unit area of land in organically selected lines compared with conventional check cultivars.…”
Section: Yield and Yield Componentsmentioning
confidence: 76%
“…Kernel number per unit area of land, on the other hand, was greater for farmer selections (data not shown), indicating greater sink strength (Entz and Fowler, 1990). Wiebe et al (2017) observed greater kernel production per unit area of land in organically selected lines compared with conventional check cultivars. As a Table 6.…”
Section: Yield and Yield Componentsmentioning
confidence: 84%
See 2 more Smart Citations
“…Bindraban et al [ 43 ] described that sink capacity is the result of biomass at anthesis and grain production efficiency (GPE). Previous studies have also shown that enhanced sink capacity can be achieved by increasing spike dry matter or SPI and GPE [ 44 48 ]. In the present research, compared with W U , W J reduced leaf size and LAI, and thus decreased biomass at anthesis, but W J improved the allocation of biomass to spike at anthesis, manifested by a higher SPI and GPE, subsequently increasing sink capacity ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%